DOES GREEN SUPPLY CHAIN INNOVATION HAVE AN IMPACT ON REVISED FIRM VALUATION? - Ario Wicaksono, Dading Damas; Rahardja, Liana; Florencia Irena Lawita; Euro Priasaddha Dhammika Lie (Media Riset Akuntansi, Auditing & Informasi, 2025)
This study investigates how green supply chain innovation affects corporate value. Accelerated industrial growth has contributed to rising air pollution levels, which in turn exacerbate global warming. As a response, companies can adopt environmental management accounting practices and adjust operational strategies to help address these challenges. However, academic discussions present differing views. Some argue that such initiatives enhance resource efficiency, while others contend that they incur substantial costs. This study employs a quantitative approach, utilizing secondary data sourced from the financial and sustainability reports of companies listed on the SRI-KEHATI index of the Indonesia Stock Exchange, with a sample of 24 companies during 5 year period. The analysis is conducted using multiple linear regression techniques. The research results show that green procurement innovation, green process innovation, and green product innovation have a positive effect on the value of the company that has undergone the latest modifications for not only product base, but service base need to be involve. The theoretical objective of this study is to contribute deeper understanding to the field of environmental accounting, with a particular focus on innovation within the manufacturing, mining, and service sectors. From a practical perspective, findings demonstrate how green practices can impact a company's overall value.